Smoking, glutathione S transferase polymorphisms (GSTM1 & GSTT1) and their association with selected inflammatory biomarkers - Sangeeta Singh; Basant Joshi; Aman Saini; Tapan Mohapatra (Al Ameen Medical College, 2022)
Introduction: In the United States (US) & other countries cigarette smoking (CS) continues to be the more preventable cause of disease and death. Glutathione S-transferase (GST) enzyme is implicated in the detoxification of carcinogens present in tobacco smoke and consequent polymorphisms in this gene may confer susceptibility to systemic diseases if DNA damage is important in various diseases. The presences of a gene-deletion polymorphism have shown by genetic studies on GSTT1 & GSTM1. Elevated tumor necrosis factor alpha (TNF α) & high sensitivity c-reactive protein (hs-CRP) has been increasingly used as a surrogate marker of systemic inflammation in diverse conditions. Lipoprotein (a) Lp(a) is a low-density lipoprotein (LDL)- like plasma lipoprotein composed of apolipoprotein B (apoB) and a large glycoprotein termed apolipoprotein (a) [apo (a)]. We investigated the associations of GST (M1 or T1) genotypes, exposure to smoking, and their interaction with selected markers of inflammation. Materials & Methods: The present study was carried out in the Department of Biochemistry, Santosh Medical College, Ghaziabad. Estimation was done including serum TNF-α by ELISA, hs-CRP & Lp(a) by turbidimetric immunoassay. DNA was extracted from serum and the GSTM1 and GSTT1 polymorphisms were determined using a simple polymerase chain reaction (PCR). Results: Out of total 284 cigarette smokers, GSTT1 gene was present in 51.1% & absent in 48.9% subjects whereas GSTM1 gene was present in 59.9% & absent in 40.1% subjects as compared to age & sex matched non cigarette smokers. These differences were found to be statistically significant (p<0.05). The mean serum TNF-α, Lp(a) & hs-CRP levels were significantly raised in cigarette smokers as compared to non-smokers. These differences were found to be statistically significant (p< 0.05). Conclusion: In conclusion, the finding of a significant association between inflammatory markers, GSTM1 and T1 with smoking status may influence systemic diseases including cardiovascular diseases via DNA damage.